Nonprescription Bleaching versus Home Bleaching with Professional Prescriptions: Which One is Safer? A Comprehensive Review of Color Changes and Their Side Effects on Human Enamel - Omar, Farhana; Ab-Ghani, Zuryati; Rahman, Normastura Abd; Halim, Mohamad Syahrizal (European Journal of Dentistry, 2019)
Objectives This study evaluates the efficacy and safety of the professionally prescribed and nonprescription over-the-counter (OTC) bleaching agents.Materials andMethods Extracted human upper central incisors were prepared and stained with red wine for 14 days before being subjected to four different bleaching agents: professionally prescribed opalescence PF 15%, VOCO Perfect Bleach 10%, nonprescription OTC Crest 3D Whitestrips, and Whitelight Teeth Whitening System. Colorimetric measurement was performed with Vita Easyshade Handheld Spectrophotometer, enamel surface microhardness measured using Vickers Hardness machine, and surface roughness was evaluated with profilometer, before and after bleaching. Scanning electron microscope (SEM) evaluation and atomic force microscopy were conducted postbleaching.Statistical Analysis The data were analyzed with t-test, two-way ANOVA, one-way ANOVA, and Turkey’s test at a significance level of 5%.Results All bleaching products have the same efficacy to whiten stained enamel. Opalescence PF 15% showed significant increase in the microhardness (92.69 ± 68.316). All groups demonstrated significant increase in surface roughness (p < 0.05). SEM evaluation showed that Opalescence PF 15% resulted in same microscopic appearance as unbleached enamel, while VOCO Perfect Bleach 10%, Whitelight Teeth Whitening System and Crest 3D Whitestrips demonstrated mild to moderate irregularities and accentuated irregularities, respectively.Conclusion Professionally prescribed bleaching agent of Opalescence PF 15% is effective tin whitening the teeth, while the other bleaching products may be effective but also have deleterious effects on the enamel.
Keywords: bleaching; home bleaching with professional prescriptions; nonprescription bleaching; efficacy of bleaching; surface roughness of enamel; microhardness of enamel